Méthodes d'Investigation De l'Alimentation Et Des Mangeurs 2021
DOI: 10.35690/978-2-7592-3347-2/c2
|View full text |Cite
|
Sign up to set email alerts
|

La mesure de la sécurité alimentaire des individus et des ménages : potentiel et défis de la collaboration entre sciences de la nutrition et sciences sociales

Abstract: Cette section s'appuie sur le cas du projet Relax 10 , un projet pluridisciplinaire (nutrition, économie, agronomie, socio-anthropologie, géographie, sciences politiques et 10. https://relax.cirad.fr (dernière consultation le 27/08/2021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…A 1994 national household survey estimated self-consumed rice production at 75% (Roubaud, 1997: 48). According to a regional 2015-2016 survey, depending on the time of year, the quantity of rice self-consumed each month varied between 18% and 98% (Bouquet et al, 2018). This can then be translated into monetary equivalents by comparing with "market" prices in order to obtain an estimate of the population's poverty levels and standard of living.…”
Section: Household Surveys Microeconomic Analyses and The Mirage Of A...mentioning
confidence: 99%
“…A 1994 national household survey estimated self-consumed rice production at 75% (Roubaud, 1997: 48). According to a regional 2015-2016 survey, depending on the time of year, the quantity of rice self-consumed each month varied between 18% and 98% (Bouquet et al, 2018). This can then be translated into monetary equivalents by comparing with "market" prices in order to obtain an estimate of the population's poverty levels and standard of living.…”
Section: Household Surveys Microeconomic Analyses and The Mirage Of A...mentioning
confidence: 99%
“…The use of nutritional scores and indices for the measurement of diversity is not a new concept; however, it is relatively recent, at least, in developing countries. Research has demonstrated a positive relationship between dietary diversity or the overall quality of food intake and the nutritional status, growth, sociocultural factors, and the diet of children and adolescents in these countries [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%